Cultural Da'wah Tuan Guru Kyai Haji. Muhammad Zainuddin Abdul Madjid (Concept, Management and Implementation in Nahdlatul Wathan Organization in Lombok, NTB) - Ahmad Sujai (Jurnal Syntax Transformation, 2023)
This dissertation examines concepts and management in the cultural da’wah of Maulana Syaikh, TGKH. Muhammad Zainuddin Abdul Madjid in Lombok, West Nusa Tenggara which was implemented at the Nahdhatul Wathan mass organization he founded. Maulana Syaikh is a charismatic scholar who has a very inspiring track record of struggle and dedication. His efforts to build the ummah through educational, social, and Islamic da’wah activities implemented through the NW and especially on the island of Lombok, are highly recognized as having had a significant influence on societal change in the region. According to the Lombok Historian, the achievements he made were the best achievements ever achieved by the Sasak people throughout history. This type of research is field research which uses descriptive analytical methods, namely presenting data that is in accordance with the research results obtained from research subjects in the field. The information and data obtained, namely by going directly to the field in accordance with the subject of this research. The instrument works by combining literature and field studies. This research uses qualitative methods with data collection techniques obtained through observation, interviews, and documentation studies. Furthermore, the collected data were processed and analyzed inductively into specific themes, then analyzed using a theoretical framework. The theoretical framework used is Giddens’ structuration theory regarding the role of agency (reflexive monitoring of action, rationalization of action, and motivation of action) and the concepts of substantives (significance, domination, and legitimacy). This research aims to explain the concept and management in the cultural da’wah of Maulana Syaikh, TGKH. Muhammad Zainuddin Abdul Madjid in Lombok, West Nusa Tenggara which was implemented at the Nahdhatul Wathan mass organization. Thus, this research highlights the existence of concepts and management in Maulana Syaikh’s cultural da’wah, which can actively contribute to social change related to educational, socio-cultural, and da’wah aspects through the Nahdhatul Wathan mass organization. The results of this research prove that Maulana Syaikh is a religious figure who has invariably had the concepts and management of cultural da’wah. Also, he has successfully become an active actor who enormously contributed to creating and synergizing social change in Lombok, NTB through the Nahdhatul Wathan he founded.